CLEAR ALIGNER ORTHODONTICS AND PERIODONTAL HEALTH: A CLINICAL, MICROBIOLOGICAL, AND RADIOLOGICAL ASSESSMENT OF SAFETY AND EFFECTIVENESS IN ADULT PATIENTS - Sadullaeva Gulchekhra Ilhomjon qizi (Scholar Express Journals, 2025)
Clear aligner orthodontics is a modern method of malocclusion correction using transparent removable trays, increasingly in demand among adult patients. One of its key advantages is the ability to maintain a high level of oral hygiene, which is especially important for preserving periodontal health. However, the impact of aligners on the gingiva and dentogingival junction requires a comprehensive evaluation using clinical, microbiological, and radiological methods. The aim of this study was to assess the safety and effectiveness of clear aligners in adult patients, as well as to identify potential periodontal changes occurring during orthodontic treatment. Adult patients with moderate malocclusion and healthy periodontium participated in the study. Clinical periodontal parameters, microbiological analysis of the oral cavity, and radiological diagnostics using panoramic radiography and CBCT were utilized
Keywords: Clear aligners; adult orthodontics; periodontal health